Perencanaan Investasi Pembangunan Perumahan Di Desa Pulisen Boyolali - Jawa Tengah - Suderajat, Ajining Wisnu; , Ir. H. Muhammad Nur Sahid, M.M., M.T (2016)
Location the occupancy on Boyolali City, currently was ideal for the local communities and businessman, considering shelter is one of basic needs. To the condition, so this research is needed to consumer survey with the subject of houses demand. This method used a questionnaire as a method of research on the subject of housing divided into some types. This research divided into several stages. The first phase of the housing and making a questionnaire. The second phase data collection of the questionnaire. The third stage data processing. The fourth stage of investment plan and analysis of eligibility economically. The fifth covering discussion, conclusion and recommendations. The results of the questionnaire, respondents are more dominant choose the type 75/108 as options investment. Results from analysis appropriateness of investment in planning houses with interest rates 10 % and the profit diverse .Has value NPV = 1.316.590.321,81, IRR = 24,59 %, BCR = 1,098, BEP = 79,08% (17 unit house), IP = 1,098, PP = 21 month 22 day, 15 month 18 day, ROI = 4,604% per month dan 4,114% per month. It can be concluded that the plan housing in the Pulisen Village, Boyolali, Central Java. Deserves to be implemented.